2005
DOI: 10.1080/01421590500087175
|View full text |Cite
|
Sign up to set email alerts
|

Twelve tips for authoring on-line distance learning medical post-registration programmes

Abstract: With innovation and creativity, almost anything can be delivered and assessed on-line. Successful on-line distance learning puts the needs of the learner first, and is characterized by the quality and clarity of learning and support materials, together with good tutorial and support networks. This in turn depends upon trained authors and implementation of relevant quality assured systems and processes. These pragmatic tips outline the main points, which should help prospective on-line developers and authors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
8
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 3 publications
0
8
0
Order By: Relevance
“…1 From 2003 to 2005, twenty-three articles were published in the Journal of Dental Education that described e-curriculum applications in dental school curricula. 1, From this literature and other sources, [25][26] a number of benefits of e-curriculum have been proposed (see Figure 1). A meta-analysis of 254 studies by Kulik and Kulik in 1991 indicated that computer-assisted instruction, in comparison with conventional lecture-based training, provided small learning gains (on the order of 0.3 standard devia-E lectronic curriculum, or e-curriculum, refers to computer-based learning including providing students with educational materials on DVD, online courses, electronic mechanisms to search the literature, email, and various applications of information technology including providing laptops to students, use of computer-based simulations in preclinical lab, PDAs, multimedia projection systems, and wireless classrooms.…”
mentioning
confidence: 99%
“…1 From 2003 to 2005, twenty-three articles were published in the Journal of Dental Education that described e-curriculum applications in dental school curricula. 1, From this literature and other sources, [25][26] a number of benefits of e-curriculum have been proposed (see Figure 1). A meta-analysis of 254 studies by Kulik and Kulik in 1991 indicated that computer-assisted instruction, in comparison with conventional lecture-based training, provided small learning gains (on the order of 0.3 standard devia-E lectronic curriculum, or e-curriculum, refers to computer-based learning including providing students with educational materials on DVD, online courses, electronic mechanisms to search the literature, email, and various applications of information technology including providing laptops to students, use of computer-based simulations in preclinical lab, PDAs, multimedia projection systems, and wireless classrooms.…”
mentioning
confidence: 99%
“…Curry et al . [ 47 ] and Olson et al . [ 20 ] emphasized the importance of selecting e-learning authors based on subject matter expertise.…”
Section: Resultsmentioning
confidence: 99%
“…Cook et al [ 50 ] identified potential barriers to implementation, and Olson et al [ 20 ] advised readers to develop a marketing plan for reaching end users. Curry [ 47 ], Wong [ 51 ], and Sowan [ 39 ] advocated efficient e-learning that saves the user time, compared with other forms of learning. Design: This depends on a series of difficult choices that include the types of hardware and software that best fit end-users’ needs .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations